Submanifolds in Cauchy Riemann Geometry (Journal of Mathematical Study, 2020)
In this paper I would like to make a report on the results about hypersurfaces in the Heisenberg group and invariant curves and surfaces in CR geometry. Theresults are contained in the papers [8, 9, 16] and [14]. Besides, I would also reporton the results about the strong maximum principle for a class of mean curvature typeoperators in [10].
Keywords: Heisenberg group; umbilicity; Pansu sphere; Strong maximum principle; horizontal ($p$−)mean curvature; subriemannian manifold; CR geometry; chain; Kropina metric; pseudohermitian geometry; CR invariant surface area functional; singular Yamabe problem; volume renormalization.